Enhanced cadmium phytoremediation of Glycine max L. through bioaugmentation of cadmium-resistant bacteria assisted by biostimulation. (October 2017) - Rojjanateeranaj, Pongsarun; Sangthong, Chirawee; Prapagdee, Benjaphorn
Abstract: This study examined the potential of three strains of cadmium-resistant bacteria, including Micrococcus sp., Pseudomonas sp. and Arthrobacter sp., to promote root elongation of Glycine max L. seedlings, soil cadmium solubility and cadmium phytoremediation in G. max L. planted in soil highly polluted with cadmium with and without nutrient biostimulation. Micrococcus sp. promoted root length in G. max L. seedlings under toxic cadmium conditions. Soil inoculation with Arthrobacter sp. increased the bioavailable fraction of soil cadmium, particularly in soil amended with a C:N ratio of 20:1. Pot culture experiments observed that the highest plant growth was in Micrococcus sp.-inoculated plants with nutrient biostimulation. Cadmium accumulation in the roots, stems and leaves of G. max L. was significantly enhanced by Arthrobacter sp. with nutrient biostimulation. A combined use of G. max L. and Arthrobacter sp. with nutrient biostimulation accelerated cadmium phytoremediation. In addition, cadmium was retained in roots more than in stems and leaves and G. max L. had the lowest translocation factor at all growth stages, suggesting that G. max L. is a phytostabilizing plant. We concluded that biostimulation-assisted bioaugmentation is an important strategy for improving cadmium phytoremediation efficiency. Highlights: Cadmium (Cd)-resistant bacteria with biostimulation increased Cd bioavailability. Biostimulation with carbon enhanced bacterial growth in Cd-contaminated soil. A combination of G. max L. and Arthrobacter sp. stimulated Cd phytoremediation. Biostimulation promoted Cd uptake in G. max L. inoculated with Arthrobacter sp. Bioaugmentation and biostimulation strategies improved Cd phytoremediation.